ESTABLISHMENT OF THE ONE HOUSE ONE Jumantik PROGRAM IN ORDER TO CONTROL DENGUE FEVER (DBD) - Supriyana Supriyana; Betty Saptiwi; Hermien Rimbyastuti; Warijan Warijan (Jurnal LINK, 2016)
Control of DHF with the establishent of the program "One Jumantik One Home" is the vector control of dengue is the Aedes aegypti mosquito by increasing the participation and empowerment of community-based family for the prevention of the spread of dengue. The purpose community service is to increase the participation and empowerment of the family-based society for the prevention Dengue Fever. The benefits of community service is expected to help local authorities in the success of dengue Disease Control Program and can help people in Kramas in an effort to minimize cases of DHF. Community service is implemented in Kramas District Tembalang Semarang with representatives from each RT target in the Kramas which amounted to 30 people and was conducted in July-August 2016. This dedication method consists of three steps, preparation step, the implementation step is filled the training materials with a lecture/discussion and simulation and practice, and the evaluation step or. The Results show court of this society Formation Program One Jumantik one house has been carried out and in the process of publishing Decision Letter by Kramas Chief. Figures Free Flick (ABJ) Kramas village has not reached the minimum target of 90%.